LAW ENFORCEMENT AGAINST ACTS OF VIGILANTISM IN SOCIETY AFTER THE OCCURRENCE OF CRIMINAL ACTS (STUDY AT THE REGIONAL POLICE OF LAMPUNG PROVINCE) - Nurdianita; Lina Maulidiana (PT. ZILLZELL MEDIA PRIMA, 2026)
Vigilantism represents a social phenomenon that frequently arises as an impulsive community response following a crime, largely stemming from diminished confidence in law enforcement. Such conduct poses a significant risk of generating additional legal infractions, given that it operates independently of authorized judicial procedures. The research questions include what form of law enforcement is taken against vigilantism that occurs in society after a crime occurs within the jurisdiction of the Lampung Provincial Police, what obstacles the Lampung Provincial Police face in enforcing the law against perpetrators of vigilantism, and what efforts the Lampung Provincial Police have taken to address the occurrence of vigilantism. The research method used is normative and empirical juridical with primary and secondary data analyzed qualitatively. The results of the study indicate that law enforcement against vigilantism is carried out through criminal law mechanisms in accordance with the Criminal Code and Criminal Procedure Code, with security measures, investigations, and inquiries without distinguishing the status of the perpetrator as a manifestation of the principle of due process of law and equality before the law. This law enforcement is felt by the community through the presence of officers at the scene of the incident, action against the perpetrator, and calls for resolution through legal channels. Obstacles faced include the spontaneous and group nature of the actions, difficulty in identifying the perpetrator, limited witnesses and evidence, and the continued strong belief that vigilantism is a normal reaction. Social solidarity and family resolutions also weaken the effectiveness of law enforcement. The efforts of the Lampung Provincial Police are carried out in a preventive, preemptive, and repressive manner through legal counseling, involvement of community and religious leaders, increased rapid police response, and firm action against perpetrators. This approach aims to prevent the culture of vigilantism and increase public trust in law enforcement. The recommendations include increasing public legal awareness, optimizing professional and consistent law enforcement by the police, and providing government support through strengthening policies, infrastructure, and ongoing legal education.